Brill's Companion to the Reception of Pythagoras and Pythagoreanism in the Middle Ages and the Renaissance - Caiazzo, Irene; Robert, Aurélien; Macris, Constantinos (Brill's Companions to Classical Reception, 2022)
A wide range of specialists provide a comprehensive overview of the reception of Pythagorean ideas in the Middle Ages and the Renaissance, shedding new light especially on the understudied 'Medieval Pythagoras' of the Latin West. They also explore the survival of Pythagoreanism in the Arabic, Jewish, and Persian cultures, thus adopting a multicultural perspective. Their common concern is to detect the sources of this reception, and to follow their circulation in diverse linguistic areas. The reader can thus have a panoramic view of the major themes belonging to the Pythagorean heritage - number philosophy and the sciences of the quadrivium; ethics and way of life; theology, metaphysics and the soul - until the Early Modern times.